Speciation of Iron Using Desferal via Simple pH Change and a Single Calibration Curve: High-Throughput Optical Sensor Based on 96-Well Plates and an Overhead Book Scanner as Detector - Dimitrios Baltzis; Apostolia Tsiasioti; Constantinos K. Zacharis; Paraskevas D. Tzanavaras (Chemosensors, 2023)
In the present study we report the development of an advantageous optical sensor for the speciation of Fe(III)/Fe(II). The sensor is based on the selective reaction of Fe(III) with a Desferal (Deferoxamine) reagent at pH = 2, while both Fe(III) and Fe(II) react with the reagent at pH = 5 using an acetate/glycine buffer. In this way, frequently used extra oxidation (H2O2) or reduction (ascorbic acid or hydroxylamine) steps are avoided. Both species can be determined in the range of 25 to 150 μM using a 96-well plate platform and the instrument-free detection of the colored complex with an overhead book scanner. The LOD is 4 μM, and an additional advantage is that a single calibration curve can be utilized for quantitation. The applicability of the sensor was demonstrated by analyzing commercially available pharmaceutical formulations for quality control purposes.